Gnathia and related Hellenistic ware on the east Adriatic coast - Miše, Maja, 1978- (Archaeopress archaeology., 2015)
Gnathia ware is a painted Hellenistic type of ware with yellow, red and white decorations on the black surface of the vessels. Due to a decoration technique simpler than that on the previous red-figure vases, Gnathia ware became the most widespread type of Hellenistic ware, and also the first type of south Italian ware that was exported in large quantities outside of the main area of production. Gnathia ware takes its name from ancient Gnathia, today Egnazia in south-east Italy, where it was first discovered in 1845. The aims of this study are fourfold: to present Gnathia ware on the East Adriatic coast, to define local Issaean Gnathia production from manufacturing to distribution (including the typology of shapes and decorations), to identify other pottery workshops along the East Adriatic coast and, finally to understand the trade and contacts in the Adriatic during the Hellensitic period.